Deletion of a Single β‐Catenin Allele in Osteocytes Abolishes the Bone Anabolic Response to Loading. (March 2014) - Javaheri, Behzad; Stern, Amber Rath; Lara, Nuria; Dallas, Mark; Zhao, Hong; Liu, Ying; Bonewald, Lynda F; Johnson, Mark L
ABSTRACT The Wnt/β‐catenin signaling pathway is essential for bone cell viability and function and for skeletal integrity. To determine if β‐catenin in osteocytes plays a role in the bone anabolic response to mechanical loading, 18‐ to 24‐week‐old osteocyte β‐catenin haploinsufficient mice (Dmp1‐Cre × β‐catenin fl/ + ; HET cKO) were compared with their β‐catenin fl/fl (control) littermates. Trabecular bone volume (BV/TV) was significantly less (58.3%) in HET cKO females versus controls, whereas male HET cKO and control mice were not significantly different. Trabecular number was significantly less in HET cKO mice compared with controls for both genders, and trabecular separation was greater in female HET cKO mice. Osteoclast surface was significantly greater in female HET cKO mice. Cortical bone parameters in males and females showed subtle or no differences between HET cKO and controls. The right ulnas were loaded in vivo at 100 cycles, 2 Hz, 2500 µϵ, 3 days per week for 3 weeks, and the left ulnas served as nonloaded controls. Calcein and alizarin complexone dihydrate were injected 10 days and 3 days before euthanization, respectively. Micro‐computed tomography (µCT) analysis detected an 8.7% and 7.1% increase in cortical thickness in the loaded right ulnas of male and female control mice, respectively, compared with their nonloaded left ulnas. No significant increase in new cortical bone formation was observed in the HET cKO mice. Histomorphometric analysis of control mice showed a significant increase in endocortical and periosteal mineral apposition rate (MAR), bone‐formation rate/bone surface (BFR/BS), BFR/BV, and BFR/TV in response to loading, but no significant increases were detected in the loaded HET cKO mice. These data show that deleting a single copy of β‐catenin in osteocytes abolishes the anabolic response to loading, that trabecular bone in females is more severely affected and suggest that a critical threshold of β‐catenin is required for bone formation in response to mechanical loading. © 2014 American Society for Bone and Mineral Research